A Critique on the Book Power and Knowledge in Iran of the Islamic Era - Hamid Sajadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The tradition directs the changes and developments of Islamic society with a certain formulation of thought. Rejecting its historic rules, the tradition prevents critical questions, extends its domination to contemporary reading, and protects religion by adhering to it. The orientalist pattern and the traditional method of understanding are two important approaches in interpreting and understanding the tradition. Each of the two methods presents different perspectives and outcomes of Middle Eastern political knowledge. But none of them shows how power has shaped knowledge and products of religious thought while taking benefit of them in the favor of its own strategies and goals. None of these two methods have focused on identifying alternative political patterns that are altered and rejected in order to make the existing order the only possible model of legitimate political life. Adopting a discursive approach, the book, "Power and Knowledge in Iran, the Islamic Era", attempts to demonstrate how and through what mechanism, Islamic discourse highlights and diversifies plural concepts, and how it extends a central concept while projecting it as an absolute, beyond time and place notion. Nonetheless, the expectations resulted from adopting such a framework would go beyond that. Such expectations, being particularly based on the discursive presuppositions, are the evaluation core of this work along with other details of the text.